logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
0 votes

Solve: $xe^y dy -e^y dx=0$

$(a)\;e^y=cx \\ (b)\;cy=e^x \\ (c)\;x^2=y+c \\ (d)\;x=y^2+c $
Can you answer this question?
 
 

1 Answer

0 votes
$x dy =dx$
$\int dy =\int \large\frac{dx}{x}$
$y= \log x +c$
$y= \log c'x$
$c x =e^y$
Hence a is the correct answer.
answered Feb 3, 2014 by meena.p
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...